Exploring the Impact of Dynamic Managerial Capabilities and Supply Chain Orientation on Supply Chain Resilience: A Structural Equation Modeling Approach - Skenderi, Nagip; Krasniqi, Sylë (International Review of Management and Marketing, 2025)
Many researchers, as well as the practitioner community, have become interested in the increased sensitivity to destructive events resulting from both the internal and external environments in the supply chain. Dynamic capabilities theory (DCT) and supply chain resilience (SCR) are relatively new concepts that have recently garnered a lot of interest from academics and industry professionals. The purpose of this research is to examine, from the standpoint of dynamic capabilities theory, the relationship between supply chain resilience and supply chain orientation. The study uses survey data collected from 184 manufacturing firms. Senior managers from these companies responded to the questionnaire’s questions. Structural equation analysis indicates a positive relationship between resilience and dynamic managerial skills. Further, the structural analysis finds a positive relationship between supply chain orientation and resilience. However, the hypothesis of the moderating role of supply chain orientation is not supported.